Crystalloid Granulomas of the Parotid Gland Mimicking Tumor: A Case Report With Review of the Literature. (June 2013) - Ho, Caleb; Sasaki, Clarence T.; Prasad, Manju L.
Crystals and crystalloids may be seen in salivary glands in association with tumors and cysts. Rarely, crystalloids may lead to granulomatous reaction mimicking neoplasm and infectious diseases. We present the case of an 81-year-old man with right parotid gland swelling and a clinical and radiological diagnosis of tumor. A granulomatous inflammation was seen on intraoperative pathology. On final pathology, the parotid gland showed multiple granulomas with central cavitation and palisading histiocytes with eosinophilic intracytoplasmic and extracellular crystalloids. The crystalloids were variably shaped, needle-like, polyhedral, rhomboid, rectangular and irregular, nonpolarizable, nonbirefringent, and nonrefractile and were orange-red with trichrome and bluish-purple with Brown and Brenn stain. Remnants of a duct lining within the lesion suggested a granulomatous response to ruptured cyst contents releasing secretions supersaturated in proteins and their precipitates.